Forensic Analysis of Web Scraping Documents on Carding Forums and Shops using Latent Dirichlet Allocation: Profiling Forensic and NLP Approaches for Cybercrime Investigation - Adristi, Fikri Irfan; Prayudi, Yudi (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2025)
This research is based on the massive cybercrime activity in carding forums and carding shops. Based on the many victims and losses from these activities a cybercrime investigation action is needed by a digital forensic investigator. The purpose of this study is to develop a forensic carding investigation framework based on document analysis of web scraping results on carding forums and carding shops, which applies forensic profiling analysis methods and natural language processing based on the latent dirichlet allocation (LDA) algorithm. The tools used for web scraping in this study are WebHarvy Version 7.3.0.222. The tools used for data processing in this study are Microsoft Excel and Orange Data Mining. The conclusion of this study shows that the application of web scraping investigation techniques on carding forums and carding shops based on an carding investigation framework has been effective in collecting relevant data and analyzing the activities of cybercriminal appropriately. Overall, this study has succeeded in developing a more organized and data-driven approach to dealing with crimes in carding forums and carding shops, which can be a reference for further research and application in the field of digital forensic investigation.